Risperidone induced angioedema with concurrent EPS symptoms: a case report and review of literature - Gursharan Singh Samra; Saumitra Kant; Robert Chow (Greater Baltimore Medical Center, 2018)
Angioedema has recently been reported as a side effect associated with the antipsychotic risperidone. We report a case of dystonia with concurrent angioedema due to risperidone. A 40-year-old male with a history of schizophrenia was started on 3 mg of risperidone BID and developed perioral and periorbital edema along with increased muscle rigidity and hand tremor within 24 h of initial administration. His symptoms abated after cessation of risperidone and intravenous administration of corticosteroids and antihistamine. This case study adds to the current literature, which has already established angioedema as a dose-dependent side effect of risperidone. Moreover, this case study aims to increase awareness about the potential for the simultaneous occurrence of angioedema and extrapyramidal symptoms, and promotes vigilance among prescribers so that the life-threatening consequences of such effects can be avoided.